Development of STEAM learning media-based on coding scratch game on the material of the characteristics of living things for elementary school - Livvia Khusnul Qomatfian; Nur Ngazizah; Rintis Rizkia Pangestika (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2024)
This research aims to (1) Produce digital learning media from several STEAM (Science, Technology, Engineering, Art, and Math) disciplines based on scratch in the form of coding games on the material characteristics of living things for elementary schools, and (2) Knowing the feasibility of digital learning media STEAM based on scratch game coding on the material characteristics of living things for elementary schools. The type of research used is Research and Development (R&D) with the ADDIE model (analysis, design, development, implementation, and evaluation). The trial was conducted on 30 students of Muhammadiyah Purworejo University. The sampling technique of this research is purposive random sampling. Data collection used observation, interview, and questionnaire techniques. Data analysis techniques using quantitative descriptive statistical processing. The results of this study, namely: (1) STEAM learning media based on coding scratch games on the material of the characteristics of living things for elementary school. (2) The feasibility of STEAM learning media based on coding scratch games on the material characteristics of living things for elementary schools obtained a value in the aspect of ideas with a percentage of 95.83% very feasible category, the aspect of usefulness with a percentage of 95.00% very feasible category, the aspect of creativity with a percentage of 92.50% very feasible category, and the display aspect with a percentage of 93.33% very feasible category. Based on the results of the assessment of the aspects of ideas, usefulness, creativity, and appearance of STEAM learning media based on coding scratch games on the material of the characteristics of living things for elementary schools, it is declared feasible to apply with very feasible criteria. In addition, digital learning media can harmonize existing technological developments in accordance with the times.